Implementasi Modul Ajar Bermuatan Coding dilengkapi dengan Video Animasi Tema Alam Semesta Sub Tema Pelangi Anak Usia 5-6 Tahun Kober Peupado Malanuza - Oka, Gde Putu Arya; Wea, Rosadalima; Ita, Efrida (IMEDTECH (Instructional Media Design and Technology) e-ISNN 2580-6033, 2024)
This research is a continuation of previous development researc, which has reached the product feasibulity test stage using the ADDIE model. Therefore, the current research aims to find out the efectiveness of teching modules containing coding equipped with animate videos on the theme of the universe, sub-theme of rainbows, for children aged 5-6 years in kober peupado malanuza. Curent research needs to be carried out at the product evaluation stage according to the ADDIE model stage, the evaluation method used is the Donal Krikpatrick model. The research design for the summative evaluation stage consist of file steps, namely (1) determining the evaluation objectives: (2) choosing an evaluation method consisting of fours levels, namely: reaction, learning, behavior, result. (3) designing evaluation instrumenst: (4) data collection : (5) analysis and report of result. The instruments used were observation sheets, and interactive analysis using the milas and huberman model. Based on data obtained from coding learning activies carried out at kober peupado malanuza, very effective results were obtained through several stages, including the following: 1) reactions in coding learning obtained were 28% debugging, 57% abstraction ,and 14% abstraction. 2) the reaction to the coding learning procces obtained was 85% decomposition, 14%decomposition. 3) reactions to children,s behavior in learning coding 57% debugging, 14% debugging 4) reactions children.s learning outcomesin learning coding 70% pattem recognition